A Comparative Study of the Influence of Body Mass Index on Clinical Outcomes of Total Laparoscopic Hysterectomy in Birat Medical College Teaching Hospital, Morang, Nepal - Neupane, Bhanubhakta; Karki, Gyanendra Man Singh; Pokharel, Hanoon P; Dahal, Prerana; Bhandari, Garima (Birat Journal of Health Sciences, 2021)
Introduction: Although laparoscopy is a safe route of hysterectomy as it provides battier view of abdominal anatomy, facilitates meticulous hemostasis and reduces surgical morbidity, laparoscopic hysterectomy in overweight and obese women may pose an increased risk of intraoperative and postoperative complications as omental fat and limited manipulation of instruments may render operation difficult. Objectives: The aim of the study is to evaluate the impact of Body Mass Index (BMI) on the clinical outcome of total laparoscopichysterectomy. Methodology: This is a comparative cross-sectional study conducted in 190 patients who underwent total laparoscopic hysterectomy (TLH) in Department of Obstetrics and Gynecology of Birat Medical College, Teaching Hospital from July, 2019 to November 2020.Ninety five patients were enrolled in high BMI group and normal BMI group each Result: Mean BMI was 28.90±2.27 ( Kg/M2)in high BMI group and 23.54 ± 1.14 (Kg/M2)in normal BMI group. Urinary tract injury occurred in 4 (4.21%) cases in high BMI group and 2 (2.1%) cases in normal BMI group. Intraoperative and immediate postoperative complication were similar in both groups. Conclusion: Intraoperative and postoperative complications were similar in both the groups. Patients with high BMI have no increased risk of complications during total laparoscopic hysterectomy.